Membrane distillation hybridized with a thermoelectric heat pump for energy-efficient water treatment and space cooling - Tan, Yong Zen (2020)
The current concept for cooling the indoors is far from ideal with respect to the total energy consumed and waste discharged. A novel concept for improving the energy efficiency is proposed via hybridizing the heat pump with a membrane distillation (MD) unit for simultaneous space cooling and water treatment. MD is well-acknowledged for utilizing low-quality waste heat for water treatment, which makes it feasible for coupling with a heat pump to make use of both the hot and cold reservoirs of the pump. Accordingly, the objective of the current effort was to investigate via experiments the efficacy of a thermoelectric heat pump coupled with a sweep-gas MD system (T-SGMD) by measuring the cooling capacity, condensate production and power consumption. The results from this study can be extended to other heat pumps. Three key highlights emanated from this study. Firstly, condensate production per unit energy consumed can be doubled with the T-SGMD system relative to thermoelectric dehumidification alone. Secondly, cool air recycle affected the condensate flux the most without a drastic loss of cooling compared to other tested parameters during the operation of the T-SGMD. Lastly, the T-SGMD system was able to provide an increase in condensate produced per unit energy without a loss in cooling capacity per unit energy input. These advantages of coupling heat pumps with MD, leveraging on the current advancements in MD, is promising for a hybridized system for decentralized water treatment, dehumidification and space cooling.